(untitled) (Linguostylistic Studies, 2020)
Modern linguistic stylistics interprets the colloquial vocabulary as a particular and unique stylistic category of an artistic text. The spoken words are contrasted with the stylistically neutral and bookish vocabulary of the literary language as the words with emotionally-expressive coloring and functional-stylistic loading. In the focus of the study is linguistic and stylistic analysis of colloquial vocabulary recorded in the novel “Heather Honey”. Extensive use of the colloquial vocabulary in the novel “Heather Honey” is a sign of the individual writing style of a Volyn writer Nadiia Humeniuk. The article explores the colloquial vocabulary of the novel as a means of stylization of the characters’ oral speech and adding subjective notes to the author’s story. The colloquial vocabulary includes words to denote the realities of mostly rural life, name-characteristics of people, actions, states, features. Spoken vocabulary is used in descriptions of everyday situations, dialogues, monologues. There are almost no part-of-speech restrictions in choosing colloquial lexemes. The colloquial elements are included in the literary text only in a spoken form, commonly used in the oral form of communication. In the literary work, colloquial words perform an informative function, because owing to them, the depicted events become vivid, correlate with the cultural-historical and spatiotemporal context of the realities of rural life of Polishchuks in the 30s of the last century. However, the main functions of colloquial vocabulary are socio-linguistic (which allows the author to accurately convey intonation of the expressions, level of education and culture of the characters), emotional, and expressive. To convey emotions, the author uses the words with low evaluative semantics, the word-forming elements with the meaning of tenderness or rudeness, which are opposed to the neutral lexemes. The expressiveness of colloquial vocabulary attracts attention, interests, causes emotional tension of the reader.